ETOS KERJA ORANG JAWA DI KECAMATAN MAKASSAR - Muh Sofyan Hidayatullah (Rayhan Intermedia, 2019)
This study aims to find out: knowing how the spirit, enthusiasm, and support of Javanese work in the Sub-district of Makassar, knowing how the Javanese interact with local communities in Makassar Sub-district, and knowing how Javanese develop work and business strategies in Makassar Sub-District. In this study used a type of qualitative research that was analyzed and written descriptively. The technique of data collection is done by using the method of observation, interviews, and documentation by involving as many as 10 informants. Based on the results of the study showed that: (1) the spirit, enthusiasm, and work support of Javanese people in the Makassar sub-district were the work spirit believed by the Javanese namely unyielding and abstinence and upholding honesty and having the principle of not working certainly not eating then spirit hard work and also supported by adequate transportation. (2) the Javanese interaction the researcher divides into three parts, namely in the social, work and marital relationships where in the Javanese relations that are intertwined with the local community are classified as harmonious between the two, but in relations in the work there is still a little conflict, and also some of them have had kinship. (3) As for the Javanese work and business strategies that he has built, that is, each individual has a different work strategy depending on the individual.